5 - The Nature and Scope of Production Sub-contracting in Nigeria: 10.4314/ad.v28i2.22178 - Ajayi, Dickson Dare (Africa Development, 2003)
This study analyses the nature and scope of production sub-contracting link ages in Nigeria. The basic concepts are integration and industrial linkage, and production subcontracting. Data for this study were collected from the 68 contracting firms among the 15 industrial estates/areas in the Lagos region. The study's finding shows that the dominant form of sub-contracting is speciality sub-contracting. The various products of sub-contracting among the industrial estates/areas in the Lagos region, and between the Lagos region and the rest of Nigeria are discussed. Independent sub-contracting is the most common type of sub-contracting relationship. While over 50 percent of the contractors engage the services of a maximum of two subcontractors, it is only in motor vehicles and the miscellaneous assembly industry group that production sub-contracting accounted for more than 30 percent of the total costs of production. It accounted for about 20 percent in each of all the other industry groups in any of the years under consideration. Furthermore, this study shows that production sub contracting carried out over relatively short distances became very important after the introduction of the Structural Adjustment Programme (SAP) in Nigeria, and it is perceived as most useful in reducing the costs of production.